The Effectiveness of Reloud Model in Increasing Knowledge and Literacy of Health Reproduction’s Adolescents Based on Health Education in Samarinda City - Zulkifli Umar; M. Ardan; Dwi Riyan Ariestantia (Poltanesa, 2023)
Reloud aims to foster students' love for reading. Indonesian adolescent sexual reproductive health research states that 10% of those aged 15-24 have had premarital sex, used condoms (49% of women & 27% of men), had unwanted pregnancies 24%, knowing that their friends had abortions ( 23% of girls and 19% of boys) and 15% of them consume alcohol, this is influenced by various factors, one of which is the lack of information about adolescent reproductive health. Literacy in Indonesia is included in the low category (37.32%), so efforts to increase literacy are very urgent to be carried out as an effort to improve the quality of the Indonesian nation's resources. The target population in this study was health-based senior high school students in Samarinda City. The design of this study used a Quasi Experiment with a pre-posttest approach with a control group design. Samples were taken from as many as 3 (three) health-based schools in Samarinda city with a purposive sampling of 60 respondents. Characteristics of the dominant respondent are 16 years old (31.6%), female (65%), and in class X (38.3%). The results of data analysis on differences in the level of adolescent reproductive health knowledge obtained a p-value of 0.826 if no intervention was given, a p-value of 0.153 if given 1 (one) intervention, and a p-value of 0.001 if given 2 (two) Reloud interventions. Of the three groups that described the effectiveness of the Reloud intervention method, it occurred significantly in increasing adolescent knowledge related to reproductive health by a p-value of 0.031 so this method is one that can be applied to adolescents.